Use of a Primary Epithelial Cell Screening Tool to Investigate Phage Therapy in Cystic Fibrosis - Trend, Stephanie; Chang, Barbara J.; O’Dea, Mark; Stick, Stephen M.; Kicic, Anthony; , WAERP; , AusREC; , AREST CF (Frontiers in Pharmacology, 2018)
Antimicrobial-resistant microbes are an increasing threat to human health. In cystic fibrosis (CF), airway infections with Pseudomonas aeruginosa remain a key driver of lung damage. With few new antibiotics on the development horizon, alternative therapeutic approaches are needed against antimicrobial-resistant pathogens. Phage therapy, or the use of viruses that infect bacteria, is one proposed novel therapy to treat bacterial infections. However, the airways are complex microenvironments with unique characteristics that may affect the success of novel therapies. Here, three phages of P. aeruginosa (E79, F116, and one novel clinically-derived isolate, designated P5) were screened for activity against 21 P. aeruginosa strains isolated from children with CF. Of these, phage E79 showed broad antibacterial activity (91% of tested strains sensitive) and was selected for further assessment. E79 genomic DNA was extracted, sequenced and confirmed to contain no bacterial pathogenicity genes. High titre phage preparations were then purified using ion-exchange column chromatography and depleted of bacterial endotoxin. Primary airway epithelial cells derived from children with CF (n=8, age range 0.2–5.5 years, 5 males) or healthy non-CF controls (n=8, age range 2.5–4.0 years, 4 males) were then exposed to purified phage for 48 hours. Levels of inflammatory IL-1, IL-6 and IL-8 cytokine production were measured in culture supernatant by immunoassays and the extent of cellular apoptosis was measured using a ssDNA kit. Cytokine and apoptosis levels were compared between E79-stimulated and unstimulated controls, and, encouragingly, purified preparations of E79 did not stimulate any significant inflammatory cytokine responses or induce apoptosis in primary epithelial cells derived from children with or without CF. Collectively, this study demonstrates the feasibility of utilising pre-clinical in vitro culture models to screen therapeutic candidates, and the potential of E79 as a therapeutic phage candidate in CF.